Climate Change, Extreme Events and Disaster Risk Reduction Towards Sustainable Development Goals (Sustainable Development Goals Series, 2018)
This book discusses the science, causes, impacts and risk reduction strategies for climate change and disasters. It focuses on the use of traditional knowledge, new innovation and education to build a culture of safety and resilience at all levels in order to promote sustainable development goals in general and disaster risk reduction in particular. The global climate has changed substantially over the last century. There is strong evidence of global climate change in the form of increase in air and sea surface temperature, recession of glaciers, changes and shifting of climate regimes, increasing number of extreme events and sea levels changes. The increasing frequency of climate change induced disasters in particular is posing a threat to resilience, lives and livelihoods at global, regional and local levels. Major ecosystems of the world have experienced several climate induced disaster events in recent past. This book provides new insights into the occurrence and impacts of climatic extremes and strategies for disaster risk reduction. It includes studies on rainfall and temperature trends, floods and drought disasters, weather and climatic related disasters in mountains, changes in plant activities, risk assessment and responses in different ecosystems of the world. The book is particularly useful for environmental and disaster managers, researchers and graduate students, as well as policy makers.